Llanos de Mojos, Bolivien. Siedlungsplätze im nördlichen Tiefland Boliviens - Prümers, Heiko (e-Forschungsberichte des DAI, 2023)
The Bolivian-German project in the Llanos de Mojos is designed to shed new light on prehispanic settlements in the region. During the last years the main focus has been on mapping and excavation of settlements associated with complex ditch-systems in the northeastern part of the Llanos de Mojos. At Jasiaquiri, a small village near the town of Baures, limited excavations revealed the existence of a hitherto unknown archaeological culture.